14. HAMBATAN PEMERINTAH INDONESIA DAN ECPAT DALAM MENANGANI PARIWISATA SEKS ANAK MELALUI RAN PTPPO DAN ESKA - Silvia Novi; Ika Riswanti Putranti; Nadia Farabi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Indonesia has become the second largest country in Asia after Thailand in child sextourism. The situation will increase every year because the tourists migrated from Thailandto Indonesia, since Thailand implement the Child Protection Act’s amendment in theircountry. These conditions make this research made for knowing obstacle from IndonesianGovernment and ECPAT’s efford in resolve child sex tourism crimes through RAN TPPOand ESKA 2009-2014. After research conducted using collective action teory,implementation of policy teory, and an explanatory method, researcher found there areobstacle in the implementation of the RAN TPPO and ESKA 2009-2014. These obstaclescome from groups of people who abuses the system, where the group of people helptourists to get child, or they sell the women and children by reason of giving them job. Theobstacle also come from the implementation of the policy, where there is no clearregulatory standards, target in the policy not comprehensive, and bad conditions in theeconomic and social sectors of society.